2015
DOI: 10.1128/aac.04773-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Spectrum of Pexiganan Activity When Tested against Pathogens from Diabetic Foot Infections and with Selected Resistance Mechanisms

Abstract: Pexiganan, a 22-amino-acid synthetic cationic peptide, is currently in phase 3 clinical trials as a topical antimicrobial agent for the treatment of mild infections associated with diabetic foot ulcers. Bacterial isolates from the 2013 SENTRY Antimicrobial Surveillance Program designated as pathogens from diabetic foot infections (DFI) and Gram-negative and -positive pathogens from various infection types that harbored selected resistance mechanisms/phenotypes were tested against pexiganan in reference cation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 12 publications
1
42
0
1
Order By: Relevance
“…Pexiganan has been shown previously to exhibit broad-spectrum activity (Flamm et al, 2015;Fuchs et al, 1998;Ge et al, 1999b;Ge et al, 1999a) (Ge et al, 1999b). When isolates from patiets with diabetic foot infections from two clinical trials were tested, MIC results were similar to those above (Ge et al, 1999a).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Pexiganan has been shown previously to exhibit broad-spectrum activity (Flamm et al, 2015;Fuchs et al, 1998;Ge et al, 1999b;Ge et al, 1999a) (Ge et al, 1999b). When isolates from patiets with diabetic foot infections from two clinical trials were tested, MIC results were similar to those above (Ge et al, 1999a).…”
Section: Discussionmentioning
confidence: 53%
“…Those diabetic foot isolates were not selected for any particular resistance pattern. In that study (Flamm et al, 2015), there were several Enterobacteriaceae isolates with MIC values >256 µg/mL for pexiganan, and in this study there were three gram-negative isolates with PMB MIC values of >4 µg/mL which also had elevated pexiganan MIC results (≥1024 µg/mL). Further study of pexiganan activity against PMB-resistant bacteria will be necessary to determine how frequently elevated MIC values to both these agents would occur together among Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As topical antimicrobial agents, both ebselen and PXL150 are still in preclinical development. However, another emerging topical antimicrobial agent is pexiganan, a cationic peptide that is in phase 3 clinical development for topical use (190,191). Clinically, pexiganan has been evaluated against systemic ofloxacin for the treatment of mildly infected diabetic foot ulcers, and it demonstrated clinical and microbiological equivalence in one study involving 835 patients (192).…”
Section: Emerging Topical Antibacterial Agentsmentioning
confidence: 99%
“…Pexiganan has a broad spectrum of activity against Gram-positive and Gram-negative pathogens (193), and it is thought to act by interacting with the negatively charged lipid bilayer, inducing toroid-like pore formation and subsequent disruption of the bacterial membrane (194). In vitro studies have shown good activity against S. aureus, CoNS, and S. pyogenes, with minimal development of resistance on serial passage at sub-MIC concentrations and no apparent cross-resistance to other commonly used topical agents, such as mupirocin and fusidic acid (190,191).…”
Section: Emerging Topical Antibacterial Agentsmentioning
confidence: 99%